Building the Modern Albanian State on Oriental Mentality - Lika, Hazbi (European Journal of Multidisciplinary Studies, 2021)
This paper aims at proving that the discourse that promotes our national identity is grounded on the new political context which initiated after the Declaration of Independence and the formation of the first Albanian state. During such a discourse, in the given period, prevails the debate on: the west openly rejects the orient. The elite that was active in politics seems to be more restrained, while the intellectual one, especially those educated in the Austro-Germanic region, declare open war on the Orient. The Political Assembly of Prizren and Vlora bring evidence of an ethnic identity which is changeable with respect to the new environment created. Albanian elites, especially the intellectual ones in the light of orientalist, rightly denounce the orient and oriental culture by not appreciating the historical environment in which our ethnic identity had to be maintained for a period of five centuries. The discourse of this period shows that our national identity began to become quite different adapting to the new reality that was created.